BISNIS, KEKUASAAN, DAN IDENTITAS (Studi terhadap Perilaku Politik Etnis Tionghoa di Bangka Belitung Pasca Orde Baru) - , IBRAHIM,S.FIL., M.SI., Prof. Dr. Nunung Pradjarto, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Tionghoa ethnic has become phenomenon in electoral political world since reformation rolled over. This situation beckoned that it occurs political behavior changing in Tionghoa ethnic body. During this time, Tionghoa ethnic that tends to be a-political, right now even enters in different situation. Nonetheless, to what extent this changing has been occurred, becomes interesting question, as interesting as question on how the earlier political behavior experiencing adaptation and continuation. This study focused on question in terms of how Tionghoa political behavior in Bangka Belitung Islands Province is. This question was then closely related to identity that had become never-ending issue of this ethnic. Itâs also interesting to discuss on how then business arena standing in the middle of that political behavior. The main focus of this study discussion was traced through qualitative study with elite approaches. Elite was chosen by considering that it is the crucial element of a community with its characteristic as the âdetermining peopleâ. Data collection was conducted by in-depth interview, participative observation, and documentation. This study also used constructivism perspective seeing that Tionghoa political elites reproduce, reduce, choose, and negotiate their identity within flexible and situational political sphere. This study generated several important findings. First, there are two main tracks chosen by Tionghoa political elites in Bangka Belitung Islands Province, they are formal and informal track. Formal track is taken by conducting politics within electoral and party realm with the primary orientation on business interest and democratization shadowed by class and existence change over. While, informal track is taken by embedding influence on power for business agenda expansion interest. Above all two tracks, identity and financial are two important instruments playing. Second, understanding Tionghoa political behavior means understanding how three discussion points play each other: enhance and sustain in the form of political pyramid, i.e. business, power, and identity. All three interplay and play complexly. Third, constructivism perspective that becomes this study mind frame needs to consider other perspectives in analyzing identity politics. Identity was not only constructed, but also instrumented. It could not be denied, however, that the given classification is primordial sentiment and attachment factor that also become part of primordial perspective. Determination perspective thus deserves to consider. This study proposed perspective combination in analyzing identity politics called âtriple perspectiveâ.